A Rare Case of Elbow Synovial Cyst with Radial Nerve Compression - Ting-Hsuan Hsu; Yen-Nung Lin (Diagnostics)
Elbow synovial cysts are rare and can mimic more frequently encountered disorders such as lateral epicondylitis, presenting diagnostic challenges. This report describes a woman in her mid-40s with persistent pain and weakness in her right forearm due to a synovial cyst compressing the radial nerve at the Arcade of Frohse. Despite initial suspicions of lateral epicondylitis, deeper investigation using sonography confirmed the presence of a compressive synovial cyst. Ultrasound-guided aspiration of the cyst was performed, yielding clear synovial fluid and providing symptomatic relief. Post-procedure imaging showed a significant reduction in cyst size and alleviation of nerve compression. This case highlights the critical role of integrating sonography with clinical evaluations in diagnosing and managing atypical presentations of neuropathic pain and motor weakness. This advanced imaging capability not only effectively facilitated an accurate diagnosis but also enabled a targeted therapeutic intervention, thereby avoiding extensive surgical procedures and reducing the risk of nerve injury.